Collective Properties Extend Resistance to Photobleaching of Highly Doped PluS NPs. Issue 44 (13th September 2017) - Genovese, Damiano; Rampazzo, Enrico; Zaccheroni, Nelsi; Montalti, Marco; Prodi, Luca
Abstract : Dye‐doped nanoparticles (NPs) are intriguing fluorescent systems in which collective properties can arise, which are ascribable to the ensemble of dyes rather than to individual ones. Collective properties can be tailored to increase brightness and introduce photophysical versatility. In this context, self‐quenching has long been regarded as the phenomenon to avoid. Here we report on the possibility to profit from a property stemming from self‐quenching: nanoparticles with a high number of dyes per NP (including self‐quenched dyes) display much slower photobleaching compared to nanoparticles with a lower doping degree. In this way, their emission intensity can be kept almost constant for ten times longer. This extended duration of luminescence is due to preferential photobleaching of self‐quenched fluorophores. These observations can shine new light on the use of highly dye‐doped nanoparticles as long‐lasting, super‐photostable probes under strong excitation conditions. Abstract : Highly dye‐doped nanoparticles are shown to be long‐lasting, super‐photostable probes under strong excitation conditions. Self‐quenched dyes act as intensity "buffers", keeping the brightness constant for a long period of time. The observed phenomenon is a collective property arising from the fast communication between dyes and the resulting preferential photobleaching of self‐quenched fluorophores.